MAHASISWI HIJABERS - Muhamad Arpah Nurhayat (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2018)
The rule of wearing veil is set by Allah in Al - Qur’an which aims to protect and keep off women from impaired lust and men’s bad stare. In its implementation, most Muslim women have different styles in wearing it. The difference caused by their difference of understanding and point of views as to veil. As if to support the difference, every Ulama has different perception about women’s aurat limitation. The difference veil implementation is happened as well on IQT’s female students of Ushuluddin and Islamic Thought Faculty. This difference occurs because some factors like family, campus environment, boarding house, and their own understanding toward meaning and veil’s goal.